Evaluasi Kinerja Keuangan Perusahaan Dengan Menggunakan Metode Economic Value Added Pada PT Alkindo Naratama Tbk - Rima Rosmelia; Etti Ernita Sembiring (Jurusan Akuntansi Politeknik Negeri Bandung, 2020)
The establishment of the Asean Economic Community (AEC) requires every company to increase its capabilities, so performance measurement is needed. Measurement of financial performance can be assessed using the Economic Value Added (EVA) method. Thus, the problem of how the financial performance of PT Alkindo Naratama Tbk is formulated when viewed using the EVA method, the goal to determine the condition of the company's financial performance when reviewed using the EVA method. The research used a qualitative method with a descriptive quantitative approach. The data collection technique is documentation study, the type of qualitative and quantitative data, the data source secondary data. Based on the research that has been carried out, the company's financial performance can be said to be quite good. Based on the results of EVA which is always positive (EVA> 0), it means the company is able to create added value and return appropriate investment to investors.